Restoring Sight to Blinding Love: The Bhāgavata Purāṇa's Transformation of the Urvaśī–Purūravas Narrative. (13th June 2018) - Gupta, Ravi M
Abstract: The narrative of King Purūravas and the heavenly damsel Urvaśī is one of the oldest love stories in the world, with a staying power that few others can claim. The account of their love, separation, and, in most versions, their eventual reunion has been reinvented throughout Sanskrit literature, beginning with the Ṛgveda. Nevertheless, the considerable attention given to the Urvaśī–Purūravas narrative in the Bhāgavata Purāṇa is surprising, given that the story has no obvious Vaiṣṇava elements; Purūravas is mentioned in five chapters of the Bhāgavata and the story is told twice, in Books Nine and Eleven. This article explores the Bhāgavata's unique rendition of the story, paying particular attention to the Aila-gītā, Purūravas' heartrending song in Book Eleven. The essay argues that the Bhāgavata is keenly aware of the Ṛgvedic version—in its language, motifs, and its refusal to entertain a happily-ever-after ending. In particular, the Bhāgavata uses the final verse of Ṛgveda X.95 as a theological springboard to transform Purūravas into a renouncer-devotee, whose life becomes another instance of the 'second-chance' narratives so loved by the Purāṇa.